INTRODUCTION TO SPECIAL ISSUE: Administrative Study in Sulawesi Selatan, Indonesia - Patak, Andi Anto (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
The special issue of Gnosi Journal: An Academic Journal of Human Theory and Praxis features a subset of papers written by researchers within the field of public administration in the South Sulawesi province of Indonesia. This special issue explicated on some important issues germane to both the ‘private’ and ‘public’ organisations within the South Sulawesi province of Indonesia.